Lactobacillus Reuteri DSM 17938 (Limosilactobacillus reuteri) in Diarrhea and Constipation: Two Sides of the Same Coin? - Saviano, Angela (Medicina (Kaunas), 2021)
Background and Objectives: Lactobacillus reuteri DSM 17938 (L. reuteri) is a probiotic that can colonize different human body sites, including primarily the gastrointestinal tract, but also the urinary tract, the skin, and breast milk. Literature data showed that the administration of L. reuteri can be beneficial to human health. The aim of this review was to summarize current knowledge on the role of L. reuteri in the management of gastrointestinal symptoms, abdominal pain, diarrhea and constipation, both in adults and children, which are frequent reasons for admission to the emergency department (ED), in order to promote the best selection of probiotic type in the treatment of these uncomfortable and common symptoms. Materials and Methods: We searched articles on PubMed(®) from January 2011 to January 2021. Results: Numerous clinical studies suggested that L. reuteri may be helpful in modulating gut microbiota, eliminating infections, and attenuating the gastrointestinal symptoms of enteric colitis, antibiotic-associated diarrhea (also related to the treatment of Helicobacter pylori (HP) infection), irritable bowel syndrome, inflammatory bowel disease, and chronic constipation. In both children and in adults, L. reuteri shortens the duration of acute infectious diarrhea and improves abdominal pain in patients with colitis or inflammatory bowel disease. It can ameliorate dyspepsia and symptoms of gastritis in patients with HP infection. Moreover, it improves gut motility and chronic constipation. Conclusion: Currently, probiotics are widely used to prevent and treat numerous gastrointestinal disorders. In our opinion, L. reuteri meets all the requirements to be considered a safe, well-tolerated, and efficacious probiotic that is able to contribute to the beneficial effects on gut-human health, preventing and treating many gastrointestinal symptoms, and speeding up the recovery and discharge of patients accessing the emergency department.